factors determining pricing strategies in Iraqi business market – on analytic study in a number of industrial sector companies - علي, نعمة شليبة; علي, حنان صفاء (Journal of Economics and Administrative Sciences, 2016)
Pricing has an important position among the elements of marketing mixture (4ps) as it represents revenues that in turn represent one of the important  pillars' for resources affecting on organizations sustainability and development , and the failure in determining prices and their strategies has a dangerous effect on the organizations reality and future as a whole . from this point,  this is what from the focus of the research problem,which centered on how to get companies to critical price that satisfies customers and achieve corporate objectives.                           This study is considered important because of pricing importance as it represents the resource that contributing in achieving companies objectives (under research ) and enhancing their effectiveness , competition and position in the market . a number of industrial sector companies are chosen ; and the test of correlation and effect hypotheses for pricing strategy are adopted in this study . the sample tested is of the managers of industrial sector of ( Al- zawraa General company , Iraqi cement company , modern dyes company , General construction company , and chemical industries company ) . data is collected of (102 ) managers of the companies management , and questionnaire is used as an essential tool for data collection , in addition to that , personal interviews are made in the companies for the study sample . a number of computerized statistical techniques in spss system are used for handling data , and the factors effecting in them and their determinants .The most important conclusions of this study are , the companies lack for marketing departments , their pricing strategies are not clear , there is an effect of lawful and government factors on pricing directions . the study has recommended the necessity of decreasing government constraints on pricing for these companies, and choosing clear strategies suitable for the market and competition.